Effect of task specific thiocyanate based ionic liquids on relative volatility of cyclohexane and benzene azeotropic mixture - Gonfa, G. (Elsevier B.V., 2017)
The relative volatilities of cyclohexane (Cy) to benzene (Bz) in the presence of eight task-specific imidazolium thiocyanate ionic liquids (ILs) were measured using headspace gas chromatography. The ILs contain nitrile, ally, benzyl and hydroxyl functional group in their imidazolium cations and thiocyanate as anion. The effects of incorporation of nitrile, allyl, benzyl and hydroxyl functional groups in imidazolium alkyl chain on the relative volatility of Cy to Bz were investigated using experiment and quantum calculations. COSMO-RS model was used to study the polarity (charge distribution) of the ILs and the solutes. Density functional theory (DFT) was employed to investigate the cation-anion interaction energies and IL-Bz/Cy binding energies. The structural variations of the imidazolium cation influence the performance of the ILs. Moreover, the performances of the ILs were compared with two typical conventional entrainers, dimethyl sulfoxide (DMSO) and N,N-dimethylformamide (DMF). Except two hydroxyl containing ILs, the remaining six ILs show higher Cy to Bz relative volatility values compared to the bench marked conventional solvents. © 2017